Exploring employer branding in Malaysia banking and hotel industries - Mohamad, Siti Fatimah; Md Sidin, Samsinar (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
The employer brand studies that have been conducted to employees are sprouted in the academic and industrial literature. Nonetheless, little qualitative investigation has been made to explore the employer brand from the perspectives of employers in hotel and banking industry. This study explored the components of employer brand that have been implemented in organizations as perceived by the human resource managers. In-depth interviews were conducted to four managers from reputable hotels and banks in Malaysia. Seven themes of employer brand were extracted from the findings: learning and growth, organization culture and management, work environment, credibility and reputation, reward and recognition, job security, and social-oriented. These themes are believed to be the employer brand dimensions that are able to attract and retain employees, from the perspectives of employers. On the other hand, from the perspectives of employees, only three employer brand dimensions were identified based on a quantitative study. The three dimensions are organization, individual, and growth. Implications of identifying the employer brand dimensions are discussed in this paper.